1992
DOI: 10.1007/bf00174851
|View full text |Cite
|
Sign up to set email alerts
|

Decolourization of olive mill waste-waters by the white-rot fungus Phanerochaete chrysosporium: involvement of the lignin-degrading system

Abstract: The decolourization of olive mill waste-waters (OMW) by Phanerochaete chrysosporium was investigated. OMW decolourization occurred during the primary phase of growth when glycerol was used as the carbon source, and during secondary metabolism in nitrogen-limited cultures. The decolourization was found to be extensive (7407o of colour removal, 80070 of chemical oxygen demand removal) when the cultures were supplemented with veratryl alcohol and flushed with 02. The biodegradation system was repressed with gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
1
9

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 25 publications
(16 reference statements)
3
61
1
9
Order By: Relevance
“…Aissam et al [13] argued that the degradation of phenolic compounds of olive mill wastewater using Aspergillus niger HA37was due to the possible action of various enzymes, including those of laccase, tannase and the ligninolytic oxidative enzymes, and demonstrated that the growth of Aspergillus niger in diluted olive mill wastewater resulted in a 70% degradation of the phenolic compounds. However, tannase probably was the principal enzymatic system of color removal because Aspergillus niger had a low LiP activity and Sayadi and Ellouz [5] have demonstrated that low LiP activity did not efficiently decolorized OMW.…”
Section: Study Of Enzymes Responsible For Topw Decolorizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Aissam et al [13] argued that the degradation of phenolic compounds of olive mill wastewater using Aspergillus niger HA37was due to the possible action of various enzymes, including those of laccase, tannase and the ligninolytic oxidative enzymes, and demonstrated that the growth of Aspergillus niger in diluted olive mill wastewater resulted in a 70% degradation of the phenolic compounds. However, tannase probably was the principal enzymatic system of color removal because Aspergillus niger had a low LiP activity and Sayadi and Ellouz [5] have demonstrated that low LiP activity did not efficiently decolorized OMW.…”
Section: Study Of Enzymes Responsible For Topw Decolorizationmentioning
confidence: 99%
“…The aerobic treatment of wastewaters was shown to be an encouraging way to reduce their toxicity and dark color [4][5][6]. The removal of color has been carried out by many fungal strains such as Aspergillus sp., which can decolorize [7][8][9][10] and / or biosorb recalcitrant compounds [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…3 The use of enzymes in waste treatment includes the decolorization of olive mill waste waters, 4 decolorization of an artificial textile effluent, 5 polymerization of pentachlorophenol, 6,7 degradation of azo, triphenyl and heterocyclic dyes, 8,9 and upgrading corn straw for paper pulping. 10 Mushrooms utilize a variety of lignocellulosic residues and convert them into human food.…”
Section: Introductionmentioning
confidence: 99%
“…Chrysosporium is one of the organisms whose ligninolytic enzyme system has been studied extensively. Because of its high ligninolytic activity, rapid growth, and ability to produce asexual spores, several biotechnological applications were tested using this particular species (Sayadi and Ellouz, 1992;1993).…”
Section: Introductionmentioning
confidence: 99%
“…A recent work has shown that the P. Chrysosporium species is able to degradate a wide variety of phenolic compounds (Sayadi and Ellouz, 1992;1993). Besides P. Chrysosporium produces two types of extra-cellular peroxidases involved in lignin biodegradation:…”
Section: Introductionmentioning
confidence: 99%